Optical Characteristics and Composition OF Cd1 – xMnxTe Films Obtained by the Close Spaced Sublimation Technique - V.V. Kosyak; A.S. Opanasyuk; P.V. Koval; P.M. Fochuk; V.V. Starikov (Журнал нано- та електронної фізики)
Study of the optical properties of Cd1 – xMnxTe films obtained by the close spaced sublimation technique was carried out. Measuring of the optical characteristics of the layers was performed by the spectrophotometric analysis method near the “red boundary” of the semiconductor photoactivity. This research allowed to obtain the spectrum distributions of the transmission T(λ), reflection R(λ) and absorption α(λ) coefficients of the films as well as estimate the band-gap energy of the compound. The values of the band-gap energy were used for determination of manganese concen-trations in the films depending on the growth conditions.